Pegaruh Kejelasan Sasaran Anggaran Dan Sistem Pelaporan Terhadap Akuntabilitas Kinerja : Studi Pada BPKAD Kabupaten Merangin (International Forum of Researchers and Lecturers, 2024)
This study aims to determine the effect of clarity of budget targets and reporting systems on performance accountability at the Regional Financial and Asset Management Agency (BPKAD) of Merangin Regency. This research uses quantitative methods and a causal associative approach, data collection techniques using questionnaires and the sample in this research was 47 employees at BPKAD Merangin Regency using purposive sampling techniques. Data analysis techniques are using descriptive statistics, data quality testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The results of this research partially show that the variables clarity of budget targets (X1) and reporting system (X2) have a significant effect on performance accountability (Y). Meanwhile, simultaneous testing shows a significant positive influence on performance accountability at BPKAD Merangin Regency.